E-Learning in the Digital Era: Evolution, Implementation, and Impact on Higher Education in Indonesia - Widya Fadhila Utami (Ilmina: Journal of Education and Counseling, 2025)
The rapid development of information and communication technology has fundamentally transformed the educational landscape, placing e-learning, or electronic-based learning, as a core component. This article analyzes the evolution of e-learning from its initial emergence in the 1960s to its crucial role in the modern digital era, including the Industrial Revolution 4.0 and its impact following the COVID-19 pandemic. This qualitative research examines how e-learning has been implemented at various levels of education, from schools to higher education, and highlights its advantages and disadvantages. Particular focus is placed on a case study of e-learning implementation at Wiralodra University (Unwir). The results demonstrate that e-learning offers flexibility in time and place, access to global resources, cost efficiency, personalized learning, and increased digital literacy. However, challenges such as disparities in technology access, lack of social interaction, limited practical courses, and low digital literacy remain barriers. This article concludes that e-learning is a crucial pillar in future educational transformation, requiring adaptive strategies to maximize its potential and overcome obstacles.